2018
DOI: 10.3389/fphys.2018.01418
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Myostatin and the GH/IGF-1 Axis in Body Composition and Muscle Strength

Abstract: Myostatin, a negative regulator of muscle growth, is considered a potential therapeutic agent for individuals suffering from various muscle wasting and strength declining diseases because inhibiting Mstn signaling leads to muscular hypertrophy. In this study we investigate the interaction between myostatin and the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis in muscle function and strength. To this end, we measured hind limb grip strength and myostatin levels in two mouse models of GH gene manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…GH is involved in the regulation of skeletal muscle growth mainly through insulin growth factors. It can increase skeletal muscle mass but has no noticeable effect on muscle strength ( 116 ). Notably, GH can increase the risk of fluid retention and insulin resistance and adversely affect the cardiovascular system.…”
Section: Joint Intervention Of Sarcopenia and Cvdsmentioning
confidence: 99%
“…GH is involved in the regulation of skeletal muscle growth mainly through insulin growth factors. It can increase skeletal muscle mass but has no noticeable effect on muscle strength ( 116 ). Notably, GH can increase the risk of fluid retention and insulin resistance and adversely affect the cardiovascular system.…”
Section: Joint Intervention Of Sarcopenia and Cvdsmentioning
confidence: 99%
“…The depletion of 4E-BPs is associated with perturbed energy metabolism in skeletal muscles, and it has also been suggested that 4E-BP can be a target of sarcopenia intervention [158]. The use of growth hormone receptor knockout (GHR −/− ) and bovine GH mice provided evidence that the insulin-like growth factor 1 (IGF-1) signaling pathway predominantly regulates myostatin, which is a negative regulator of myogenesis [159]. The correlation between mitochondria and muscle atrophy has been elucidated using Opa1 −/− mice.…”
Section: Genetically Engineered Animal Modelsmentioning
confidence: 99%
“…This gene was found to be expressed most strongly in ovary and liver and was strongly up-regulated in the breeders´ ovaries and adrenal glands (Table 1). IGF1 codes for a well-known key regulator of anabolic effects such as cell proliferation, myogenesis, and protein synthesis (Schiaffino and Mammucari 2011;Jung and Suh 2014) and has a tight functional relation to GH (gene: GH1) another key anabolic regulator upstream of IGF1; together, these factors form the so-called GH/IGF1 axis (Cannata et al 2010;Junnila et al 2013;Bodart et al 2015;Raisingani et al 2017;Carotti et al 2018;Lozier et al 2018). Also, GH1 was strongly up-regulated in breeders in its known principal place of synthesis, the pituitary gland (Table 1).…”
Section: Resultsmentioning
confidence: 99%